Community-based Environmental Communication for Disaster Mitigation on Peatlands in Bengkalis Regency, Indonesia - Yasir Yasir; Ibrahim Johan Afendi; Nurjanah Nurjanah; Samsir Samsir (E3S Web of Conferences)
Bengkalis Island and Bengkalis Regency generally have peatlands that are mostly abandoned, prone to fires and prone to landslides due to abrasion. The Environmentally Concerned Malay Youth Association (IPMPL) created a movement to cultivate Cratoxylum Arborescens (gerunggang) as a native plant to prevent fires. This research aims to explore community-based environmental communication for disaster mitigation in peatlands. The method applied in this research is a case study. The research results show that the environmental campaign is based on the problem of peatlands which are vulnerable to fires and landslides due to abrasion. IPMPL plays a role in campaigning for peatland conservation through gerunggang cultivation. This movement contributes to mitigating fire disasters in peatlands and abrasion landslides. Environmental communication based on Forest Farmer Groups (KTH) contributes to reducing the risk of land fires and can improve the community’s economy. This community collaborates with several parties such as: the Ministry of the Environment, Forest Management Units (KPH), district and provincial governments, as well as farming community groups in campaigning for environmental messages. This collaboration contributes to reducing the problem of environmental damage on peatlands. However, IPMPL has not maximized the use of social media to publish all its activities.